Caring as a moral practice: an analysis of the construction of care for elderly people in Austria and the UK - Weicht, Bernhard (2010)
This thesis investigates the meaning of care in our societies. Everyone will be concerned with care in some way at some point in his/her life. In the UK and Austria economic and social developments challenge traditional family arrangements while the need for care for the elderly is increasing. But how do we understand care and which meaning does care have for us, for our relationships, for our identities and for our understanding of society? How do we want to live together, and how do we want to experience the process of ageing? Understanding the construction of care helps to understand aspects of people’s ideals, motives, attitudes, imaginations, aspirations and desires in life.